Estudos fitoquímicos de espécies do gênero Bauhinia (Fabaceae) da região Amazônica - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Species of the genus Bauhinia are used in various parts of the world to treat various diseases, especially for the treatment of diabetes due to hypoglycemic activity has proven to Bauhinia forficata species, which is associated with the presence of the flavonoid kaempferitrina. However, other species also have the same effect and this is associated with the presence of other flavonoids glycosides. In this study we sought to prepare the phytochemical profile of four species of Bauhinia Amazon region from their crude extracts, alkaloid and flavonoics fractions in order to promote an initial scan for more specific biotechnology projects. Furthermore, Bauhinia coronata (Manaus-AM), B. purpurea (Manaus-AM), B. acreana (Manacapuru-AM) and B. purpurea (S. Gabriel da Cachoeira) were analyzed for antioxidant activity front free radicals DPPH., ABTS.+ and O2-, as well as the inhibition of enzymes lipoxygenase, α-amylase, lypase, α-glycosidase and tyrosinase. Among these assays as biological antioxidants and tyrosinase and α-glycosidase, stood the species B. coronata and B. purpurea with lower values for IC50 (IC50 of B. coronata leaf’s crude extract: 1.91 ± 0.55 μg / mL). The toxicity of crude extracts was also tested against Artemia salina, with LD50 values of greater than 250 μg/mL, indicating the low toxicity of them. However, the analysis of their potential cytotoxic and antibacterial no species has been active, which is contrary to reports in the literature that Bauhinia purpurea was mentioned with these potentials. The profile of flavonoids were identified, using TLC, HPLC-DAD-UV and mass spectrometry, and the rutin and isoquercitrin flavonoids in the species B. coronata and B. purpurea, the latter being related to the flavonoid has hypoglycemic activity of other species of Bauhinia, and anti-inflammatory action. The kaempferitrin flavonoid wasn’t found in any species, as no substance of the alkaloidal class. The results from the antioxidant activity, low toxicity and the presence of flavonoids with potential herbal stimulate future research for specific biotechnological purposes.
Keywords: Bauhinia; Rutina; Isoquercitrina; Flavonoides; Cromatografia; Rutin; Isoquercitrin; Flavonoid; Chromatography; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA